STRATEGI PENINGKATAN KINERJA BANDARA INTERNASIONAL SYAMSUDIN NOOR BANJARMASIN BERBASIS DAYA TARIK DENGAN INOVASI SEBAGAI VARIABEL MODERATING - Mujiatin, Yeni; Derriawan; Sihite, Mombang (SEKOLAH PASCASARJANA PRESS, 2021)
The objective of this study was to determine the effect of comparative advantage, ease of connectivity, and digital marketing directly or indirectly on airport attractiveness, as well as the effect of all variables on company performance moderated by the innovation of Syamsudin Noor International Airport Banjarmasin. The sample size was 255 passengers who have used services of the new airport terminal that began operations in December 2019. Sampling technique used in this study was purposive sampling. Data collection used a questionnaire. Data analysis technique used Structural Equation Modeling (SEM) processed with the assistance of SmartPLS version 3 software. The results indicated that comparative advantage variable had a significant effect on airport attractiveness. Likewise, ease of connectivity and digital marketing variables had a significant effect on airport attractiveness. However, comparative advantage had no significant effect on company performance, while other variables of ease of connectivity, digital marketing, and attractiveness had a significant effect on company performance. Comparative advantage variable through innovation had a significant effect on company performance. Ease of connectivity variable through innovation had a significant effect on company performance. Digital marketing variable through innovation had a significant effect on company performance. Attractiveness variable through innovation had a significant effect on company performance. Thus, innovation can encourage or improve company performance at Syamsudin Noor International Airport Banjarmasin. The result also shows that the airport performance improvement strategy plan refers to the strategies from the analysis that has been carried out and the right strategy is chosen to be compiled into work plans and programs. Not only until the work program, the result also captured Key Performance Indicators (KPI) related to the intended strategic goals.